'MGNREGA and Right to work: A Study of Malda District of West Bengal' - Roy, Chandan (Indian Journal of Political Science)
In order to ensure the right to work, the Government of India has at various times undertaken a number of rural development and poverty alleviation programs. The purpose of these program is to increase job opportunity in rural areas. Most of the previous programs were withdrawn or converged with other schemes due to poor plan implementation policies, insufficient funding/ budget allocation or widespread corruption. In 2005, the then UPA-I government introduced the National Rural Employment Guarantee Scheme in the Parliament, which aims to help all rural aspiring households to provide at least 100 days guaranteed wage employment a year at a minimum stipulated wage rate and help to alleviate poverty by protecting rural people from unemployment. The most significant aspect of this scheme is that all willing adult rural people can register their name under this scheme and demand for work whenever their require. In other words, this program is completely demand driven and self- centric. This program is quite effective in a backward, underdeveloped agrarian district like Malda district and where the population is settled densely but remains rural in character. In this study the researchers tried to show how MGNREGA plays an important role in alleviating poverty in the district by solving the problem of unemployment by implementing the right to work.- Reproduced
Keywords: poverty, unemployment, demand driven, MGNREGA, Right to Work